The quest for economic stabilization : the IMF and the third world - Killick, Tony.; Bird, Graham R. (New York : St. Martin's Press, 1984)
The book is an examination of the IMF in the general context of economic stabilization in developing countries, and their policy recommendations.
Companion vol. to: The IMF and stabilization. 1984.
Includes index.
Includes bibliographical references: p. [321]-331.
rua 25/05/17
Loans
Keywords: Economic stabilization; Balance of payments; Developing countries